The role of masonry infills on the damage response of R/C buildings subjected to seismic sequences. (15th January 2017) - Morfidis, Konstantinos; Kostinakis, Konstantinos
Highlights: The damage of infilled 3D buildings subjected to sequential earthquakes is studied. Various structural types with different distribution of masonry infills are analyzed. Nonlinear time response analyses for variable incident angles are performed. The successive earthquake phenomenon on the damage is larger for infilled buildings. In case of infilled buildings it is crucial to account for the incident angle. Abstract: Reinforced Concrete (R/C) buildings with masonry infills are amongst the most common structural systems in many countries with regions of high seismicity. The infill walls are usually considered as non-structural elements and, thus, are not taken into account in analytical models. However, numerous researches have shown that they can significantly affect the seismic response of the structures. Moreover, historical earthquakes have shown that successive seismic events may occur in regions of high seismicity. Such a sequence of earthquakes has the potential to increase the damage level of the structures, since any rehabilitation between the successive ground motions is practically impossible due to lack of time. The aim of the present study is to examine the role of masonry infills on the damage response of 3D R/C buildings with various structural systems subjected to seismic sequences. For the purposes of the above investigation a comprehensive assessment is conducted using 54 3-dimensional R/C buildings with different heights, structural systems and distribution of masonry infills. The buildings are analyzed by means of nonlinear time history analysis for 80 bidirectional seismic sequences. In order to account for the influence of the incident angle on the structural response, the two horizontal accelerograms of each ground motion are applied along horizontal orthogonal axes forming 12 different angles with the structural axes. The results revealed that the influence of the successive earthquake phenomenon on the structural damage is larger for the infilled buildings compared to the bare structures. Furthermore, when buildings with masonry infills are analyzed for seismic sequences, it is of great importance to account for the orientation of the seismic motion.